Analisis Mikrobiologi Produk Tenggiri Beku (Scomber japonicus) di Balai KIPM Jakarta II - Ilva Viola; Junianto (Jurnal Serambi Engineering, 2025)
Microbiological tests were carried out to analyse the quality of frozen mackerel products based on food safety standards. The aim of this study was to assess the microbiological quality of frozen mackerel samples coded 0357/I, 0388/I, 0113/N, 0145/N and 0173/N by testing for the presence of Escherichia coli, Listeria monocytogenes and Salmonella spp. using methods from SNI 2332.1:2015, SNI ISO 11290-1:2012 and SNI ISO 6579-1:2017. The results showed that Escherichia coli, Listeria monocytogenes and Salmonella spp. were not detected in any of the samples tested. These results indicate that the products meet food safety standards and reflect the application of good hygiene practices and hygienic production processes. The absence of pathogenic bacteria also suggests that low-temperature storage effectively prevents bacterial growth. Based on these results, frozen mackerel products are considered to be of good quality, safe for consumption and in compliance with international standards.